Schweigen - eine vergessene Tugend für christliche Führungskräfte. Kirchners Ansatz aus freikirchlicher Perspektive betrachtet / Silence - a forgotten virtue for christian leaders. Kirchner’s approach from a free-church perspective - Kessler, Volker (University of Pretoria, 2026)
Dissertation (MTh (Practical Theology))--University of Pretoria, 2024.